Managing Approach the Workload Balance Over Workstations at Stage Process Engineering Part-Making in Multi-Product Production - Grigoriev Sergey (EDP Sciences, 2021)
This paper shows the features of workflow distribution on workplaces on the technical process preparation stage of parts production and the operational and calendar planning stage. Also, the problem of workflow distribution on workplaces was formulated and the mechanism of its occurrence was described. An algorithm for managing the distribution of the volume of work by jobs at the stage of technological preparation of production was developed.